Report on Spalding Investigation, - Geary, Edward R., 1811-1886
In early 1872, H. H. Spalding and H. T. Cowley sent letters of complaint against J. B. Monteith, the Indian agent at the Lapwai Agency. In March 1872, E. R. Geary made an inspection trip to Lapwai and had a number of people answer questions in writing. This collection contains eight letters and the report that Geary wrote concerning those accusations in April 1872. Letters are present from Geary to the Commission of Indian Affairs (a copy) and original letters from Greenleaf, Wesley Mulkey, Navid Noggle, Alonzo Leland, H. Adams. The first page of Geary' report is missing. Geary's report stated that he found no evidence of the charges of "debauchery, gross profanity, and habitual intemperance" that had been made against Perrin Whitman, interpreter at Lapwai, and that Monteith was administering the agency with "integrity and efficiency."